Activation of NLR-Mediated Autoimmunity in Arabidopsis Early in Short Days 4 Mutant - Huang, Xingchuan; Liu, Yanan; Huang, Jianhua; Fernando, W. G. Dilantha; Li, Xin; Xia, Shitou (Frontiers in Plant Science, 2022)
From a reverse genetic screen using CRISPR/Cas9 gene editing tool, we unintentionally identified an autoimmune mutant. Map-based cloning and whole-genome sequencing revealed that it contains a deletion in SMALL UBIQUITIN-RELATED MODIFIER (SUMO) protease encoding gene EARLY IN SHORT DAYS 4 (ESD4). Previous studies indicated that elevated salicylic acid (SA) level partially contributes to the constitutive PR1 expression in esd4 plants. Here we show that N-hydroxypipecolic acid (NHP) biosynthetic genes are also upregulated in esd4, and NHP biosynthesis mutant fmo1 partially suppresses the autoimmune phenotypes of esd4, suggestive of a requirement of NHP signaling for the autoimmunity in esd4. Further genetic analysis revealed that EDS1 is largely responsible for autoimmunity of esd4, as eds1 blocks the constitutive defense response of esd4. In addition, eds1 largely blocks the elevated expressions of SA and NHP biosynthesis-related genes in esd4. Overall, our study provides evidence supporting the hypothesis that SUMO protease ESD4 likely targets a yet to be identified guardee of NLR by removing its SUMO modification to avoid recognition by the cognate NLR. Loss of ESD4 results in activation of NLR-mediated autoimmunity.